(untitled) (Research, Society and Development, 2020)
In developing countries, as the case in Brazil, the elderly is understood like people with 60 years old or more, and the psychological theories of aging have been possible only in the last 60 years, with the temporal extension of human life and its consequent eld. In this research was made a bibliographic study with publications by classic and contemporary authors about the principal psychological theories of aging. The psychological theories of aging are subdivided into three categories, being 5 classical theories, 2 transition theories and 6 contemporary theories. The Classical Psychological Theories presented are: The Course of Human Life, Disengagement theory, Developmental tasks and life history, Continuity theory and Phases of Psychological Development troughout Life. The Transitional Psychological Theories are: Stages of Psychosocial Development and Social-Interacionist Theory of personality in old Age. And Contemporary Psychological Theories are: life-span and life-course, Theory of Selection, Optimization, and Compensation, Behavioral or learned addiction, Socioemotional selectivity theory, Life-span theory of control and Critical Life Course Events. Is it clear that the psychological theories about aging have changed over time, influenced by the socio-historical context and also by the maturation of representations about aging.